2021
DOI: 10.21203/rs.3.rs-653536/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of Depression with Sperm Quality: a Multicentre Cross-Sectional Study in China During the COVID-19 Pandemic

Abstract: Background: Depression is a potential factor affecting semen quality. However, the relationship between depression and semen quality remains to be fully elucidated. We investigated the association between depression and semen quality in men during the COVID-19 pandemic.Methods: Cross‐sectional, participants completed a questionnaire assessing lifestyle factors the Patient Health Questionnaire-9 (PHQ-9) was used to evaluate the psychological depression status of subjects. Semen quality assessment implements the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Several studies have investigated the relationship between depression, anxiety, and stress and their impact on sperm quality. The findings from the research conducted by Wang et al [32] involving 896 individuals, revealed a correlation between depression and semen characteristics (such as semen concentration, semen volume, total sperm count, and progressive motility of sperm) in males. Additionally, they observed a nonlinear decrease in depression in relation to semen volume and progressive motility of sperm.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have investigated the relationship between depression, anxiety, and stress and their impact on sperm quality. The findings from the research conducted by Wang et al [32] involving 896 individuals, revealed a correlation between depression and semen characteristics (such as semen concentration, semen volume, total sperm count, and progressive motility of sperm) in males. Additionally, they observed a nonlinear decrease in depression in relation to semen volume and progressive motility of sperm.…”
Section: Discussionmentioning
confidence: 95%